Identity's Moments: The Self in Action and Interaction - Perinbanayagam, Robert (Lexington Books, 2012)
The work is an examination of the role of language in the constitution of self and in the presentation of identity. Following the path laid out by George Herbert Mead, Kenneth Burke and Mikhail Bakhtin the work presents self, identity and meaning as ongoing accomplishments between human actors who participate in what may be termed the dramas human relations. Human agents use language as symbolic actions with which they transform themselves and others, as well as places and things, clothing and money etc into meanings with which they conduct their lives.